PENGARUH PERBEDAAN DOSIS LARUTAN PUPUK NPK MAJEMUK TERHADAP KEBERHASILAN PERTUMBUHAN BAWANG MERAH (Allium ascalonicum L.) - Khusna Amalia Damayanti; Prasodjo Soedomo (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
This research aims to determine the type of shallot variety and the correct dosage for maximum growth and yield of shallot plants. The research method used an experimental method with the experimental design used was a single factor randomized block design (RBD) consisting of 6 treatments, namely A (Sembrani Variety and 100). ml/polybag), B (Sembrani variety and 120 ml/polybag), C (Sembrani variety and 140 ml/polybag), D (Mente's variety and 100 ml/polybag), E (Mente's variety and 120 ml/polybag), and F (Mente's variety and 140 ml/polybag) was repeated 4 times so that there were a total of 24 experimental units. The effect of the treatment was analyzed using variance and if the F test at the 5% level was significant, then to find out the best treatment was continued with the DMRT (Duncan Multiple Range Test) further test at the 5% level. The results showed that there was a significant effect on the types of shallot varieties with different dosages of NPK compound, on all research parameters. Treatment E gave the highest yield at plant height (44.49 cm), the weight of fresh tubers with leaves/clump (7.11 g), the weight of fresh tubers with leaves/plot (19.93 g), the weight of dry tubers with leaves/clump (5.90 g), weight dry tubers with leaves/plot (16.35 g). While treatment D gave the highest yield on the number of tillers (3.14), the number of leaves (6.97), the number of tubers (3.14). Treatment C gave the highest yield on tuber diameter (22.58 mm) and treatment A tuber length (31.48 mm).